The Impact of Functional Integration and Spatial Proximity on the Post-entry Performance of Knowledge Intensive Business Service Firms - Andreas Koch; Harald Strotmann (Institut für Angewandte Wirtschaftsforschung (IAW), 2005)
Knowledge intensive business service firms (KIBS) are an important element of modern economies and thus attracting increasing interest in scientific research. In the existing literature it is argued that due to the important role of knowledge, innovation and userproducer interaction in the KIBS sector, functional integration and spatial proximity are particularly decisive for a firm?s development. Nevertheless, due to the absence of suitable micro data there is a lack of studies empirically analysing the impact of functional integration and regional proximity using micro firm data. Based upon newlyconducted firm micro data in three German metropolitan regions, this paper supplements the literature by giving a multivariate empirical analysis of the determinants of post-entry performance of KIBS. The results of the estimation of firm growth equations show that functional linkages to knowledge providers, customers and co-operation partners indeed matter for the performance of young KIBS. Regarding spatial proximity, however, especially a high diversification of geographical reach is proved to be crucial.
Keywords: O30; L80; J23; D21; 330; Employment growth; Entrepreneurship; Entry; Firm growth; Innovation; Knowledge intensive business services; Post-entry performance